Principal transformational leadership and teacher readiness to teach: Mediating role of self-efficacy - Akhmad Arif Musadad; Raden Bambang Sumarsono; Maulana Amirul Adha; Nova Syafira Ariyanti; Nur Fatah Abidin; Dadan Adi Kurniawan (International Journal of Evaluation and Research in Education (IJERE), 2022)
Student should participate in high-quality learning regardless of all existing conditions; therefore, efforts are needed to identify various factors related to teacher readiness in teaching (TR). This research identified the effect of the four components of transformational leadership (TL) on teacher TR in the era of the coronavirus disease 2019 (COVID-19) pandemic through the role of teacher self-efficacy mediation. The study used a quantitative approach, with a model of structural equation modelling (SEM) causality with the help of the analysis of moment structure 24.0 (AMOS 24.0) program. This study involved 332 secondary school teachers as respondent. SEM is used to build relationship models and to analyze direct or indirect effects, while the Sobel test is conducted for testing mediation hypotheses. Based on the results of research, four components of TL, can affect teacher TR through teacher self-efficacy. The contribution of this research provides insight into the importance of the principal's TL practices in preparing teachers for teaching through teacher self-efficacy, which is a necessity today.